Их, дээд сургуулийн гадаад хэлний сургалтанд цахим сургалтын арга хэрэгслийг ашиглаж буй асуудалд: On the situation which use emethod foreign language training in the institutes - B., Enkhbold (Mongolian Journal of Foreign Languages and Cultures, 2023)
Podcasts can be used for several educational purposes. Podcast are great alternatives for delivering research content or lessons to students who need remedial or extended support, Students can create their own podcast to share their learning experiences with each other and also with other students from other schools.Teachers can record audio podcast to provide additional and revision material to students to download and review at a time that fits them the best. Podcast can hugely benefit auditory learners and help them in their learning. Creating podcast allows students to develop several important skills such as researching, writing, speaking effectively, solving problems, managing time, grabbing attention and improving their vocabulary.